Search for physics beyond the standard model in events with τ leptons, jets, and large transverse momentum imbalance in pp collisions at [Formula: see text] - CMS Collaboration; Chatrchyan, S; Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Aguilo, E; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; et al. (The European physical journal. C, Particles and fields, 2013)
A search for physics beyond the standard model is performed with events having one or more hadronically decaying τ leptons, highly energetic jets, and large transverse momentum imbalance. The data sample corresponds to an integrated luminosity of 4.98 fb-1 of proton-proton collisions at [Formula: see text] collected with the CMS detector at the LHC in 2011. The number of observed events is consistent with predictions for standard model processes. Lower limits on the mass of the gluino in supersymmetric models are determined.